The Effectiveness of Problem-Based Learning in Improving Critical Thinking and Emotional Intelligence of Students at SMK Negeri 3 Barru - Saparuddin; Sitti Aminah; Ahdar (IAIN Parepare, 2025)
This study aims to find out: How the Problem-Based Learning (PBL) strategy is implemented by Islamic Religious Education (PAI) teachers at SMK Negeri 3 Barru; How to develop students' critical thinking skills and emotional intelligence after participating in PAI learning using PBL strategies; and the influence of PBL strategies on students' critical thinking skills and emotional intelligence. This study uses a quantitative approach with a quasi-experimental method. Data collection techniques include tests, questionnaires, and documentation. Data analysis was carried out through normality, homogeneity, t-test, and Multivariate Analysis of Variance (MANOVA) tests with the help of the SPSS for Windows version 26.0 program. The results of the study showed that: The Problem-Based Learning Strategy was implemented in three main stages, namely before, during, and after treatment. The stage before treatment includes instrument validity testing and pre-test implementation. The implementation stage includes context-based learning activities on authentic religious issues, collaborative group discussions, exploration of Islamic sources, presentation of results, and joint reflection, with teachers acting as facilitators. The average score of students' critical thinking skills increased from 53.10 to 69.10, while the average emotional intelligence increased from 53.10 to 67.75 after the implementation of the PBL strategy. The results of the multivariate test (MANOVA) showed a significance value of 0.000 on all indicators (Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's Largest Root), which indicated a significant influence of the Problem-Based Learning strategy on improving the critical thinking skills and emotional intelligence of students at SMK Negeri 3 Barru. These findings confirm that the application of Problem-Based Learning strategies in PAI learning is not only effective in improving students' critical thinking skills, but also able to develop their emotional intelligence, which contributes to character formation and reflective thinking skills in the context of religious education in vocational schools.